P058: Improving patient safety and streamlining care at a community hospital through spread and scale of a trauma care bundle: a quality improvement pilot project. (2nd June 2016) - Hahn, E.; Andres, R.; de Kok, T.; Brown, A.; Doyle, J.
Abstract : Introduction: Non-trauma centers (NTC) and community hospitals commonly deliver medical care during the "golden hour" of trauma, which has significant implications on the health outcomes of patients. The Niagara Health System (NHS) and its 3 community NTC hospitals provide trauma care to over 100 patients annually during this critical period. NTCs lack standardized resources commonly found in trauma centers. Checklists and bundles have been effective in streamlining process to ensure health care providers provide the right care, at the right time and address critical points during patient care. A trauma care bundle was designed and implemented in the NHS as a means to improve trauma care and patient outcomes.Methods: A quality improvement (QI) approach was used to design, implement and evaluate a trauma care bundle at one of the NHS's community hospitals. These interventions were adapted and modified for community trauma care purposes. We piloted the trauma care bundle using rapid cycle improvements, known as Plan-Do-Study-Act (PDSA) cycles. We assessed outcome and process measures through a chart audit of all trauma care patients in the NHS from July 2015-December 2015. A safety attitudes questionnaire (SAQ) was administered to health system staff who were involved in the pilot to assess balancing measures.Results: Improvements to the bundle and its implementation from 4 PDSA cycles resulted in increased utilization. This continuous monitoring of the bundle and ongoing, conscious efforts to improve the intervention were used to spread and scale across all 3 sites of the NHS. 30% of patients received the trauma care bundle during phase 1 of the pilot from July 1- October 31, 2015. We are presently analyzing preliminary data to understand how the trauma care bundle impacts health outcomes and process and will present a comparative analysis between patient groups.Conclusion: Trauma care bundles may foster safer and more efficient patient care in community hospitals where the golden hour of trauma often occurs. This community trauma care bundle shows promising results for streamlining the care process to ensure patients receive appropriate care during the golden hour. Spread and scale of this bundle across other community hospitals will likely yield similar improvements in patient care.